TRANSLATION TECHNIQUES USED IN THE TRANSLATION OF THE TALE OF TOM KITTEN DONE BY DHARMASISWA STUDENTS OF STIBA SARASWATI DENPASAR - Utami, Ni Made Verayanti; Devi Maharani, Putu (Sphota : Jurnal Linguistik dan Sastra, 2019)
ABSTRACT     The differences in two linguistic and cultural systems have made obstacles in translation. Thus, this research is aimed at analysing the translation technique used by the student in translating the narrative text. The data focused on the translation of The Tale of Tom Kitten from English to Indonesian done by ten students of BIPA (Indonesian for non-native speaker) Dharmasiswa at STIBA Saraswati Denpasar. The method of collecting the data in this research was direct observation method. It observed directly through the translation of the fable. There were two techniques used in collecting the data. The first was reading the English version of The Tale of Tom Kitten and the Indonesian translation done by the students. The second technique was choosing the sentences that represent the use of translation techniques in translating the narrative text. After the data collected, they were analysed through descriptive qualitative method. The data analysed were the results of the research. The translation strategies used to translate the narrative text were analysed. The techniques of analyzing the data followed three steps. First, the data represented the translation strategies use in translation was noted. Then, it was analyzed the type of the translations techniques used to translate the sentences from English into Indonesian. The result found that there were four type of techniques used by the students to translate The Tale of Tom Kitten. They are literal technique, establish equivalent technique, reduction technique, and amplification technique.   Key words:  translation techniques, narrative text, Dharmasiswa students